SEPARATION PROCESS AND APPARATUS - EVANS, KENNETH, EARNEST; ALDERSON, ANDREW; RASBURN, JOHN (1999)
The invention provides a method of separating, at least part of one or more components, from a mixture of components, the method comprising exposing the mixture to a porous barrier, the barrier being formed of a material structure having, or behaving in the manner associated with, a negative Poisson ratio. In this way, particularly through the use of auxetic materials, improved separations, improved de-fouling of barriers and a variety of other beneficial properties can be obtained. L'invention porte sur un procédé de séparation d'un mélange de composants, et d'au moins une partie d'un ou plusieurs composants. Ce procédé consiste à exposer le mélange à une barrière poreuse qui est formée dans une structure de matériau ayant un coefficient de Poisson négatif, ou se comportant d'une manière associée à ce coefficient. De cette façon, notamment par l'utilisation de matériaux auxétiques, il est possible d'obtenir de meilleures séparations, un meilleur désencrassement des barrières et une variété de propriétés avantageuses.